Project-Based Learning Assisted By Multimedia Interactive Learning Based On Ethnomathematics With Android Application To Improve Creative Thinking Abilities - Nurfaidah Nurfaidah; Emi Pujiastuti; Adi Nur Cahyono (Universitas Wiralodra, 2025)
This study aims to investigate the effectiveness of mathematics learning with interactive multimedia based on ethnomathematics through an android application in improving students' creative thinking skills. The research method used was a quasi-experimental with a non-equivalent pretest-posttest control group design on grade IX students of SMP Negeri 1 Karangampel. The selection of experimental and control classes was carried out using purposive sampling techniques. Data collection was carried out using documentation, test and interview methods. The findings of this study indicate that who used interactive multimedia based on ethnomathematics through an android application achieved classical completeness and had higher creative thinking skills and based on the average N-gain score of the experimental class and the control class, the average N-gain score for the experimental class was higher than the average N-gain score for the control class, namely 0.8022 > 0.6994 so that more significant improvements compared to students who did not use the multimedia. Thus, interactive multimedia-based PjBL can be used as a relevant and effective pedagogical approach in learning transformation geometry material.